The Case for Tradable Remedies in WTO Dispute Settlement - Bagwell, Kyle; Mavroidis, Petros C.; Staiger, Robert W. (World Bank, Washington, D.C., 2013)
In response to concerns over the efficacy of the WTO dispute settlement system, especially in regard to its use by developing countries, Mexico has tabled a proposal to introduce tradable remedies within the Dispute Settlement Understanding. The idea is that a country that has won cause before the WTO, and who is facing non-implementation by the author of the illegal act but feels that its own capacity to exercise its right to impose countermeasures is unlikely to lead to compliance, can auction off that right. The attractiveness of this idea is that it offers an additional possibility to injured WTO members to get something from the dispute settlement mechanism without putting into question the legal nature of the existing contract, that is, the predominantly decentralized system of enforcement in the WTO. Examining all disputes brought to the WTO since its inception, the authors find some support for Mexico's perception that developing countries face a practical problem when they attempt to carry through with effective retaliation within the WTO system. And based on the formal results of Bagwell, Mavroidis, and Staiger (2003), they describe arguments that lend some support to the efficacy of Mexico's proposed solution from the perspective of formal economic theory.